Do Vaccines Need a Gender Perspective? Influenza Says Yes! - Sánchez-de Prada, Laura; Ortiz de Lejarazu-Leonardo, Raúl; Castrodeza-Sanz, Javier; Tamayo-Gómez, Eduardo; Eiros-Bouza, José María; Sanz-Muñoz, Iván (Frontiers in Immunology, 2021)
Background: Sex differences in immune responses are well-known. However, the humoral response in males and females in the case of influenza vaccination is yet to be characterized since studies have shown uneven results. Methods: A retrospective study was conducted in 2,243 individuals (46.9% males) divided by age (15-64 and ≥65 years old). A serological analysis by hemagglutination inhibition assay (HI) just before and 28 days after annual vaccination against seasonal influenza viruses in people vaccinated during the 2006-2018 seasons. A comparison of the humoral responses against the influenza A and B viruses contained in the vaccine, between male and female individuals in young adults and elderly was conducted. Results: Significative higher humoral response against classical influenza A (H1N1), A(H1N1)pdm09 subtype and B/Victoria lineage in terms of seroconversion rate was found in elderly women. Conclusions: Elderly women seems to display a greater humoral response against classical A(H1N1), pandemic A(H1N1)pmd09 and B/Victoria lineage than elderly men. Sex dimorphism does not affect young adults.